[PP.19.15] DETERMINANTS OF OSA IN PATIENTS OF A HYPERTENSION CLINIC. (September 2016) - Marques, P.; Nogueira-Silva, L.; Lima, M.J.; Cunha, F.; Pereira, C.
Abstract : Objective: Obstructive sleep apnea (OSA) is characterized by repeated episodes of upper airway obstruction during sleep. Its association with hypertension (HTN) and increased cardiovascular risk is well established but it is underdiagnosed. We aimed to describe the patients submitted to sleep studies and identify OSA determinants. Design and method: Retrospective study based on clinical records from a HTN clinic of a tertiary care hospital. Demographic, biometric and clinical data was gathered; in patients submitted to sleep studies, the presence of OSA, its stratification according to apnea-hypopnea index and the indication for non-invasive ventilation was recorded. Student t tests and chi-square tests were used to compare continuous and categorical variables, respectively. A multiple logistic regression model was fitted to identify determinants of OSA. Results: A total 540 patients, aged 55.5 ± 15.9 years, 54% females, were followed in the HTN clinic. Of these, 164 (33%) were submitted to sleep studies: all had symptoms compatible with OSA, 13 (8%) had non-dipper profile, 38 (23%) had resistant HTN, 15 (9%) had both non-dipper profile and resistant HTN. In 134 (82%) a diagnosis of OSA was made; 80 (60%) were prescribed and adhered to non-invasive ventilation. Among patients submitted to sleep studies, patients with OSA had a higher BMI than those without (31 ± 4.9 vs 28 ± 6.3 kg/m2, p = 0.005). However, among patients with OSA, 10 (8%) had normal and 53 (40%) excess weight. At the moment of the sleep study, OSA patients were treated with 2.7 (1.3) drugs vs 2.2 (1.4) drugs in those without OSA (p = 0.046). Smoking habits were similar between groups. In the multivariate model, only BMI and age were independent determinants of OSA. Conclusions: In this hypertensive patients, a relevant prevalence of OSA was observed and this diagnosis was established in the majority of patients submitted to sleep studies. While BMI is an independent determinant of OSA, a relevant proportion of patients are non-obese. These results suggest that physicians treating hypertensive patients should be aware of the importance of OSA and sleep studies should be performed more often, with potential benefits regarding blood pressure control and reduction of the cardiovascular risk.